The Role of Micro-Influencer as Key Opinion Leader in Increasing Brand Awareness of Jiniso - Nisrina, Malya Risa; Sudradjat, Ratih Hasannah (Journal La Sociale, 2025)
The advancement of digital technology has transformed marketing communication patterns, particularly in the local fashion industry. This study aims to analyze the role of micro-influencers as key opinion leaders (KOL) in increasing Jiniso’s brand awareness, using the Two Step Flow Theory as its theoretical foundation. This theory posits that brand information is more effectively conveyed to the public through trusted KOLs. The research hypothesizes that collaboration with micro-influencers can foster stronger audience engagement and trust compared to conventional advertising. This study employed a descriptive qualitative approach with an interpretive paradigm. Data were collected through in-depth interviews and non-participant observation of Jiniso’s micro-influencer content on TikTok. Informants were selected by purposive sampling, involving micro-influencers, Jiniso’s marketing team, and digital marketing experts. The results show that micro-influencers build audience trust and emotional closeness through authentic, responsive, and consistent content. Soft-selling strategies, personal storytelling, hashtags, and community challenges were proven to increase brand exposure, audience engagement, and electronic word of mouth (e-WOM). These findings align with the Two Step Flow Theory and reinforce previous research on the effectiveness of KOLs in digital communication. In conclusion, the collaboration between Jiniso and micro-influencers successfully creates strong social and emotional bonds, significantly enhancing brand awareness among Generation Z. This study highlights the importance of collaborative communication strategies and adaptive influencer selection in digital marketing communication practices.